Meningkatkan Kemampuan Guru dalam Menerapkan Model Pembelajaran Problem Centered Learning Melalui Focus Group Discission di Sekolah Dasar Negeri 187/X Bangun Karya Tahun 2019/2020 - Mujiem Mujiem (Jurnal Ilmiah Dikdaya, 2020)
This research is a classroom action research that aims to improve the ability of teachers to apply the problem centered learning model of learning in the Elementary School 187/ X Bangun Karya, Academic Year 2019/2020. The subject of this study was a teacher at 187 / X Bangun Karya Elementary School, Rantau Rasau District, Tanjung Jabung Timur District, Jambi Province. This class action research was carried out in two cycles, each cycle consisting of two meetings. The results of the evaluation are converted into a recapitulation table of the results of cycle I. The conversion results state that the research has not yet reached the target, it needs to be continued with cycle II. The results of observers in the implementation phase of the second cycle showed that all parts of the learning activities were going well, so that there were no more parts of the learning activities that needed to be improved. While the results of the second cycle are converted with the results of the recapitulation table states that the study has reached the target limit of completeness criteria in the first cycle that is equal to 50% and an average of 68.7 in the initial conditions of improvement in the second cycle completeness criteria to be 100% and the average namely 91.7 states that the Focus Group Discission can improve the ability of teachers to apply the Problem Centered Learning learning model in learning in 187 / X Public Elementary School Build Work Year 2019/2020.